Preparation method of non-stoichiometric nanotube supported electrocatalyst based on electrospinning

The non-stoichiometric nanotube-supported electrocatalyst is prepared through electrospinning technology and two-step annealing process, which solves the problem of the electrocatalyst being easily dissolved under a full pH medium, and achieves efficient and stable acidic oxygen evolution reaction, which is suitable for industrial applications of electrolyzed aquatic hydrogen.

CN120465057APending Publication Date: 2025-08-12NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510565352.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The existing electrocatalysts are easily dissolved under full pH media, resulting in a decrease in catalytic activity, making it difficult to efficiently carry out oxygen evolution reactions under acidic conditions, and the ruthenium-based catalyst is unstable in actual operation.

Method used

Electrospinning technology combined with oxygen-reducing atmosphere two-step annealing process is used to prepare a non-stoichiometric nanotube-supported electrocatalyst. The nanofiber tubular transition metal oxide support is formed by electrospinning, and precious metal nanoparticles or precious metal oxide nanoskin coated precious metal nanoparticles are loaded on its surface.

Benefits of technology

It improves the catalytic activity and stability of the catalyst, can maintain efficient oxygen evolution performance in acidic media for a long time, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120465057A_ABST
    Figure CN120465057A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a non-stoichiometric nanotube supported electrocatalyst based on electrospinning, which comprises the following steps: dissolving an organic compound or transition metal salt of transition metal and an electrospinning raw material in an organic solvent for electrostatic spinning, carrying out annealing pre-oxidation treatment in air, and annealing in a reducing atmosphere to obtain the non-stoichiometric nanotube supported electrocatalyst. A transition metal oxide / NF carrier material with a non-stoichiometric ratio is obtained; and adding a noble metal salt solution, adding a surfactant and a reducing agent to react, and annealing in a reducing atmosphere to obtain the non-stoichiometric transition metal oxide / NF loaded noble metal nanoparticles. And further oxidizing and calcining in the air to oxidize the outer noble metal into noble metal oxide. The invention also discloses the non-stoichiometric nanotube supported electrocatalyst prepared by the preparation method disclosed by the invention. By adopting the preparation method disclosed by the invention, the non-stoichiometric nanotube supported electrocatalyst can be successfully synthesized, and the catalytic activity and stability of the electrocatalyst can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water electrolysis catalysts, and in particular to a method for preparing a non-stoichiometric nanotube-loaded electrocatalyst based on electrospinning, including preparing a non-stoichiometric nanotube-loaded electrocatalyst based on electrospinning technology and a preparation method thereof. Background Art

[0002] The increasing global demand for energy has doubled the demand for fossil fuels such as coal, oil, and natural gas. However, the toxic substances and carbon dioxide released by the combustion of fossil fuels have led to global environmental pollution and the greenhouse effect. To combat these increasingly serious environmental problems, a variety of renewable energy technologies, such as wind, solar, and tidal power, have been developed. However, the intermittent and cyclical nature of these renewable energy sources has posed a significant challenge to their storage.

[0003] Water electrolysis can convert electricity generated by wind and solar energy into hydrogen for storage. Moreover, as a high-energy fuel, hydrogen reacts with oxygen to produce only water, making it clean and environmentally friendly. Therefore, water electrolysis is an attractive energy conversion method. Compared with alkaline water electrolysis, the water electrolysis reaction under acidic conditions has a higher mass transfer rate (the proton exchange membrane used under acidic conditions can reach 800-2500mA·cm at 70-80℃). -2 , while the anion exchange membrane used under alkaline conditions can only reach 200 to 500 mA cm at 50 to 70 °C. -2 Therefore, the development of efficient catalysts for water electrolysis under acidic conditions has important significance for large-scale applications.

[0004] However, most known electrocatalysts cannot perform oxygen evolution reaction (OER) in harsh media with a wide range of pH values because they dissolve easily at oxidative potentials, resulting in a loss of catalytic activity. Therefore, the development of efficient and stable electrocatalysts for OER in media with a wide range of pH values is crucial for the development of the water electrolysis industry.

[0005] Although ruthenium-based catalysts (metallic Ru and RuO x ) shows high activity in OER catalysts, but under actual operating conditions, Ru-based catalysts show significant instability, with large amounts of dissolution leading to catalyst degradation as the main reason. Therefore, research on how to improve ruthenium-based catalysts or find more suitable iridium-based catalysts (metal Ir and IrO x ), in order to provide OER catalysts with high activity and stability is also the current main research direction. Summary of the Invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing a non-stoichiometric nanotube-supported electrocatalyst based on electrospinning, which is based on electrospinning technology and a two-step annealing process in an oxygen-reducing atmosphere to prepare a nanofiber tubular non-stoichiometric oxide support (Ti n O 2n-1 、W n O 3n-1 、Mo n O 3n-1 、Mn n O 2n-1 or Ce n O 2n-1 ), and load precious metal nanoparticles (Ru, Ir or Pd) or precious metal nanoparticles coated with precious metal oxide nanoskin (RuO2 / Ru, IrO2 / Ir or PdO / Pd) on its surface.

[0007] The preparation method of the defect ion anchoring-reducing atmosphere annealing-local oxidation electrocatalytic oxygen evolution catalyst provided by the present invention specifically comprises the following steps: a certain proportion of tetrabutyl titanate (or ammonium metatungstate, ammonium molybdate, manganese nitrate, ammonium cerium nitrate), methanol, acetic acid, polyvinyl pyrrolidone, polystyrene is mixed, electrostatic spinning is performed, and then high temperature annealing is performed in a reducing gas to cause a reduction reaction, and the stable metal oxide is reduced to a non-stoichiometric metal oxide. Then, the non-stoichiometric metal oxide is dispersed in water, and the noble metal ions are reduced by defect ion anchoring-reducing atmosphere annealing. The reduced ions will nucleate and grow at the defects of the carrier to form a metal element for the coating of the carrier, followed by deionized water washing, drying, air calcination oxidation, and obtaining a metal nanoparticle-based catalyst coated with a metal oxide nanoskin. Through the interaction between and the purpose of improving the catalytic activity, stability, and water resistance of the catalyst is achieved. The non-stoichiometric electrocatalyst synthesized by the present invention has an excellent catalytic performance beyond Ru / C as an oxygen evolution catalyst, and there is no obvious attenuation in the 500h stability test.

[0008] The object of the present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a non-stoichiometric nanotube-supported electrocatalyst based on electrospinning, comprising the following steps:

[0010] S1, dissolving an organic compound of a transition metal or a transition metal salt and an electrospinning raw material in an organic solvent, and mixing them uniformly to obtain an electrospinning solution;

[0011] S2, electrospinning the electrospinning solution to obtain a transition metal oxide support precursor;

[0012] S3, annealing and pre-oxidizing the transition metal oxide support precursor in air to obtain a stable transition metal oxide / CNF;

[0013] S4, annealing the transition metal oxide / CNF in a reducing atmosphere to perform a reduction reaction to obtain a non-stoichiometric transition metal oxide / NF support material;

[0014] S5, adding a non-stoichiometric ratio of transition metal oxide / NF support material to a noble metal salt solution for dispersion to obtain a mixed dispersion;

[0015] S6. Add a surfactant to the mixed dispersion, and slowly add a reducing agent in an ice-water bath to obtain a precursor solution;

[0016] S7. Filter the precursor solution, wash and dry it, and then anneal it in a reducing atmosphere to obtain the product.

[0017] As some specific embodiments of the present invention, the preparation method further comprises:

[0018] S8. Oxidatively calcining the product obtained in step S7 in an air atmosphere.

[0019] As some specific embodiments of the present invention, in step S1, the transition metal is selected from any one of titanium (Ti), tungsten (W), molybdenum (Mo), manganese (Mn), and cerium (Ce); the organic compound of the transition metal or the transition metal salt is selected from any one of an organic titanium compound, a tungstate, a molybdate, a manganate, and a cerate; further, the organic titanium compound includes tetrabutyl titanate, the tungstate includes ammonium metatungstate, the molybdate includes ammonium molybdate, the manganate includes manganese nitrate, and the cerate includes ammonium ceric nitrate.

[0020] In some specific embodiments of the present invention, in step S1, the electrospinning raw material includes polyvinyl pyrrolidone (PVP) and any one of polystyrene, polymethyl methacrylate, polylactic acid, polyvinyl alcohol, and polyacrylonitrile. Preferably, polyvinyl pyrrolidone and polystyrene are used. The relative molecular mass of the polyvinyl pyrrolidone is 100,000 to 150,000, preferably 130,000.

[0021] The introduction of polystyrene (PS) as a structural template and sacrificial pore agent promotes phase separation and decomposition of organic components during pyrolysis, effectively forming structural oxygen vacancies and mesoscopic channels, thereby enhancing electrocatalytic activity and the transport rate of reactants, significantly outperforming systems without PS. Conventional electrospinning uses only polyvinyl pyrrolidone (PVP) without PS, and the resulting structure is not porous.

[0022] In some specific embodiments, the organic compound of the transition metal includes tetrabutyl titanate, and the usage ratio of tetrabutyl titanate to polyvinyl pyrrolidone and polystyrene is (1.5-3 mL):(0.8-1.5 g):(0.1-0.3 g), preferably 2 mL:1.2 g:0.2 g.

[0023] As some specific embodiments of the present invention, in step S1, the organic solvent is a mixed solvent of methanol and acetic acid, and the volume ratio of the two is 4:3 to 6:3, preferably 5:3.

[0024] As some specific embodiments of the present invention, in step S2, the transition oxide support precursor is selected from any one of an organic titanium compound / CNF, a tungstate / CNF, a molybdate / CNF, a manganate / CNF, and a cerate / CNF, more specifically tetrabutyl titanate / CNF, ammonium metatungstate / CNF, ammonium molybdate / CNF, manganese nitrate / CNF, or ammonium cerium nitrate / CNF.

[0025] As some specific embodiments of the present invention, in step S2, the voltage of the electrospinning is 15-20 kV, preferably 17 kV, and the feeding speed is 0.3-0.5 mL / h, preferably 0.4 mL / h.

[0026] As some specific embodiments of the present invention, in step S3, the temperature of the annealing pre-oxidation treatment is 250-300° C., and the time is 1.5-3 hours, preferably 280° C., for 2 hours.

[0027] As some specific embodiments of the present invention, in step S3, the pre-oxidation is performed in a porcelain boat.

[0028] As some specific embodiments of the present invention, in step S4, the reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume ratio of hydrogen is 5-20%, preferably 5%.

[0029] As some specific embodiments of the present invention, in step S4, the annealing temperature is 900-1100° C., and the time is 1-3 hours, preferably 1000° C., for 2 hours.

[0030] As some specific embodiments of the present invention, in step S4, the non-stoichiometric ratio of transition metal oxide / NF support material is selected from Ti n O 2n-1 / NF、W n O 3n-1 / NF、Mo n O 3n-1 / NF、Mn n O 2n-1 / NF、Ce n O 2n-1 / NF, where n is an integer from 1 to 4.

[0031] The non-stoichiometric oxide nanofiber carrier is formed based on the combination of electrospinning and two-step annealing technology, which can provide a higher specific surface area and achieve high metal loading.

[0032] As some specific embodiments of the present invention, in step S5, the precious metal is selected from any one of Ru, Ir, and Pd, the precious metal salt solution is selected from any one of RuCl3, IrCl3, and PdCl2 solutions, and the concentration of the precious metal salt solution is 0.05 to 0.2 M, preferably 0.1 M.

[0033] As some specific embodiments of the present invention, in step S5, the mass volume ratio of the non-stoichiometric transition metal oxide / NF support material to the noble metal salt solution is (30-70) mg:(5-20) mL, preferably 50 mg:10 mL.

[0034] In some specific embodiments of the present invention, in step S6, the surfactant is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and hexadecyltrimethylammonium bromide. 3-aminopropyltrimethoxysilane is preferred, and its concentration is 95-99%, preferably 97%. During the metal loading process, the surfactant is used to assist metal formation and form an oxide skin by precisely controlling the annealing temperature.

[0035] In some specific embodiments of the present invention, in step S6, the reducing agent is selected from at least one of sodium borohydride (NaBH4) and sodium citrate. Preferably, an aqueous sodium borohydride solution is used, with a concentration of 0.5 to 2 M and an addition rate of 0.2 to 0.5 mL / min, preferably 1 M at 0.3 mL / min. The NaBH4 reduction combined with surfactant modification can effectively reduce the particle size of the loaded metal particles, providing more active sites.

[0036] As some specific embodiments of the present invention, in step S7, the reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume ratio of hydrogen is 5-20%, preferably 5%. Annealing in a reducing atmosphere can improve crystallinity.

[0037] As some specific embodiments of the present invention, in step S7, the annealing temperature is 300-500° C., and the time is 1-3 hours, preferably 350° C., for 2 hours.

[0038] As some specific embodiments of the present invention, the product obtained in step S7 is a non-stoichiometric ratio of transition metal oxide / NF loaded noble metal nanoparticles electrocatalyst selected from Ti n O 2n-1 / Ru、Ti n O 2n-1 / Ir、Ti n O 2n-1 / Pd、W n O 3n-1 / Ru、W n O 3n-1 / Ir、W n O 3n-1 / Pd、Mo n O 3n-1 / Ru、Mo n O 3n-1 / Ir、Mo n O 3n-1 / Pd、Mo n O 3n-1 / Ru、Mo n O 3n-1 / Ir、Mn n O 2n-1 / Pd、Ce n O 2n-1 / Ru、Ce n O 2n-1 / Ir、Ce n O 2n-1 / Pd, wherein n is an integer from 1 to 4.

[0039] In some specific embodiments of the present invention, in step S8, the calcination temperature is 300-500° C. and the calcination time is 1-3 hours, preferably 350° C. and 2 hours.

[0040] As some specific embodiments of the present invention, the product obtained in step S8 is a non-stoichiometric ratio of transition metal oxide / NF loaded noble metal oxide nanoskin coated noble metal nanoparticles electrocatalyst, selected from Ti n O 2n-1 / Ru / RuO2、Ti n O 2n-1 / Ir / IrO2、Ti n O 2n-1 / Pd / PdO2, W n O 3n-1 / Ru / RuO2、W n O 3n-1 / Ir / IrO2、W n O 3n-1 / Pd / PdO2、Mo n O 3n-1 / Ru / RuO2、Mo n O 3n-1 / Ir / IrO2、Mo n O 3n-1 / Pd / PdO2、Mnn O 3n-1 / Ru / RuO2、Mn n O 3n-1 / Ir / IrO2、Mn n O 3n-1 / Pd / PdO2、Ce n O 2n-1 / Ru / RuO2、Ce n O 2n-1 / Ir / IrO2、Ce n O 2n-1 Any one of / Pd / PdO2.

[0041] In a second aspect, the present invention provides a non-stoichiometric nanotube-supported electrocatalyst prepared by any of the methods described above. The non-stoichiometric nanotube-supported electrocatalyst is an oxygen evolution catalyst.

[0042] As some specific embodiments of the present invention, the non-stoichiometric nanotube-supported electrocatalyst is selected from Ti4O7 / Ru / RuO2, Ti4O7 / Ir / IrO2, Ti4O7 / Pd / PdO2, Ti3O5 / Ru / RuO2, Ti3O5 / Ir / IrO2, Ti3O5 / Pd / PdO2, Ti2O3 / Ru / RuO2, Ti2O3 / Ir / IrO2, Ti2O3 / Pd / PdO2, W 18 O 49 / Ru / RuO2、W 18 O 49 / Ir / IrO2、W 18 O 49 / Pd / PdO2、Mo4O 11 / Ru / RuO2、Mo4O 11 / Ir / IrO2、Mo4O 11 / Pd / PdO2, Ce2O3 / Ru / RuO2, Ce2O3 / Ir / IrO2, Ce2O3Pd / PdO2.

[0043] As some specific embodiments of the present invention, the non-stoichiometric nanotube-supported electrocatalyst is an electrocatalytic oxygen evolution catalyst, and is specifically applied to electrocatalytic oxygen evolution in acidic media.

[0044] The invention synthesizes the product through electrospinning combined with defect ion anchoring, reducing atmosphere annealing, and local oxidation, which has simple process and low cost and is applicable to large-scale industrial production.

[0045] First, a transition metal oxide support precursor (organotitanium compound / CNF, tungstate / CNF, molybdate / CNF, manganate / CNF, or cerate / CNF) is prepared by electrospinning. Acetic acid is added to prevent the hydrolysis of the organic transition metal compound or transition metal salt (such as tetrabutyl titanate). Methanol, a common organic solvent, is inexpensive, environmentally friendly, and compatible with tetrabutyl titanate. Polystyrene forms a carbon skeleton during electrospinning, while the relatively large molecular weight of polyacrylonitrile provides better viscosity for the electrospinning solution, making it easier to electrospin. Polystyrene has a low pyrolysis temperature and resides within the electrospun fiber during spinning. During the pyrolysis process, it decomposes within the electrospun fiber, forming channels and nanotubes, increasing the surface area.

[0046] Afterwards, pre-oxidation in air can better maintain the fiber structure and oxidize the organic titanium compound (or any one of tungstate, molybdate, manganate, and cerate) into a stable transition metal oxide; then high-temperature annealing in a reducing gas causes a reduction reaction to occur, reducing the stable transition metal oxide to a non-stoichiometric transition metal oxide.

[0047] Next, a non-stoichiometric transition metal oxide is dispersed in water, and the noble metal ions are reduced using a defect ion anchoring-reducing atmosphere annealing method. NaBH4 is used as a reducing agent, and the reaction temperature is lowered in an ice-water bath to slow the reduction rate. 3-Aminopropyltrimethoxysilane acts as a surfactant, which improves the bonding between the Ru, Ir, and Pd particles and the non-stoichiometric transition metal oxide.

[0048] The noble metal ions (Ru 4+ 、Ir 4+ 、Pd 2+ ) will be transformed into noble metal single-substance particles (Ru, Ir, Pd), which will nucleate and grow at the defects of the carrier, and grow evenly on the surface of the carrier. The nano-morphology of this single-substance particle is a spherical small particle of about 5nm, which has a high specific surface area, and the surface area in contact with the electrolyte is further increased to improve the catalytic activity. The reaction cycle of the method of the present invention is short, which saves time. The coordinated product is then subjected to high-temperature annealing in a reducing atmosphere to increase the crystallinity and maintain the metallic state. The electrocatalytic performance is closely related to its crystallinity. A more appropriate crystallinity can make the catalyst have good catalytic performance. A coating of the noble metal single substance on the carrier is formed. This special structure provides the prerequisite for excellent electrocatalytic performance.

[0049] Finally, through oxidation at 350°C, the outermost layer of Ru, Ir, and Pd particles will be oxidized to RuO2, IrO2, and PdO. What the noble metal-based catalyst needs to overcome is operational stability. The unsatisfactory stability of the noble metal-based catalyst is mainly due to its poor chemical stability. In the electrocatalytic reaction, Ru 4+ 、Ir 4+ 、Pd 2+ By oxidizing the outer layer of Ru, Ir, and Pd into RuO2, IrO2, and PdO, the internal Ru, Ir, and Pd elements can be wrapped up, and the oxidation and dissolution of Ru, Ir, and Pd inside the organization can be prevented, thereby increasing the service life. Moreover, the oxidation temperature of Ti4O7 is above 400°C, and the oxidation of Ru, Ir, and Pd will not cause the non-stoichiometric transition metal oxides (Ti n O 2n-1 、W n O 3n-1 、Mo n O 3n-1 、Mn n O 2n-1 or Ce n O 2n-1 ) oxidation and reduce conductivity.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] 1) The present invention reduces the stable transition metal oxide to a non-stoichiometric transition metal oxide with oxygen vacancies. Compared with the stable transition metal oxide, the non-stoichiometric transition metal oxide (Ti n O 2n-1 , W n O 3n-1 , Mo n O 3n-1 , Mn n O 2n-1 , Ce n O 2n-1 ) possesses the same excellent electrochemical stability, acid, alkali, and corrosion resistance as carbon materials. The presence of oxygen vacancies not only provides conductivity comparable to carbon materials but also provides nucleation and growth sites for the noble metals (Ru, Ir, and Pd) reduced in subsequent steps. The strong interaction between the transition metal oxide support and the noble metals significantly enhances catalytic performance.

[0052] 2) The oxygen evolution catalyst synthesized by the present invention was applied to the field of oxygen evolution in acidic media, and it was found that it had excellent catalytic performance and no obvious attenuation in long-term stability tests.

[0053] 3) The present invention uses electrospinning technology in combination with defect ion anchoring, reducing atmosphere annealing, and local oxidation strategies to synthesize non-stoichiometric transition metal oxide / NF-loaded noble metal nanoparticle electrocatalysts or non-stoichiometric transition metal oxide / NF-loaded noble metal oxide nanoskin-coated noble metal nanoparticle electrocatalysts. The preparation process is simple, the cost is low, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Other features, objects and advantages of the present invention will become more apparent upon reading the detailed description of non-limiting embodiments with reference to the following drawings:

[0055] Figure 1 This is the XRD image of the Ti4O7 / NF support material prepared in step 1 of Example 1;

[0056] Figure 2 This is an SEM image of the Ti4O7 / NF support material prepared in step 1 of Example 1;

[0057] Figure 3 The XRD pattern of the Ti4O7 / Ru / RuO2 composite material prepared in step 2 of Example 1;

[0058] Figure 4 This is an SEM image of the Ti4O7 / Ru / RuO2 composite material prepared in step 2 of Example 1;

[0059] Figure 5 This is a schematic diagram of the process for preparing the Ti4O7 / Ru / RuO2 composite material according to Example 1;

[0060] Figure 6 This is an XDR image of the Ti4O7 / Ru composite material prepared in Example 2;

[0061] Figure 7 This is an XDR image of the TiO2 / NF support material prepared in Comparative Example 1;

[0062] Figure 8 is an XDR image of the TiO2 / Ru / RuO2 composite material prepared in Comparative Example 2;

[0063] Figure 9 The electrochemical polarization curves of the electrocatalysts prepared in various examples and comparative examples in a three-electrode reaction cell in 0.5M H2SO4 electrolyte are shown;

[0064] Figure 10 The figures are constant current polarization curves of the electrocatalysts prepared in various examples and comparative examples at a current density of 10 mA in a three-electrode reaction cell and a 0.5 M H2SO4 electrolyte. DETAILED DESCRIPTION

[0065] The present invention will be described in detail below with reference to specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those skilled in the art, several variations and improvements can be made without departing from the scope of the present invention. These all fall within the scope of protection of the present invention.

[0066] Example 1

[0067] 1. Preparation of Ti n O 2n-1 / NF vector

[0068] (1) Preparation of electrospinning solution: 2 mL of tetrabutyl titanate, 1.2 g of polyvinyl pyrrolidone, and 0.2 g of polystyrene were added to a mixed solution of 5 mL of methanol and 3 mL of acetic acid and stirred evenly.

[0069] (2) Electrospinning: Electrospinning was performed at an applied voltage of 17 kV and a feed rate of 0.4 mL / h;

[0070] (3) Pre-oxidation: heating to 280°C in air for 2 h to pre-oxidize to obtain stable metal oxides;

[0071] (4) Annealing reduction: Heat to 1000°C in a hydrogen-argon mixed gas (hydrogen volume ratio is 5%) for 2 hours to obtain the product Ti n O 2n-1 / NF carrier material.

[0072] Physical property test:

[0073] The Ti prepared in this step n O 2n-1 The X-ray diffraction (XRD) and scanning electron microscopy (SEM) tests of the / NF carrier materials were carried out, and the results were as follows: Figure 1 、 Figure 2 As shown. Figure 1 It can be seen from the XRD pattern that the Ti prepared in the above steps n O 2n-1 The XRD pattern of the Ti4O7 / NF support material matches the standard card of Ti4O7, so the support material prepared in the first step of Example 1 is Ti4O7 / NF support material. Figure 2 It can be seen that the Ti4O7 / NF support material prepared in the first step of Example 1 has a nanotube morphology with a diameter of about 300 nm.

[0074] 2. Preparation of Ti n O 2n-1 / Ru / RuO2 catalyst

[0075] (1) 50 mg of the Ti4O7 / NF support prepared by electrospinning combined with high-temperature reduction in the above step was dispersed in 10 mL of 0.1 M RuCl3 aqueous solution;

[0076] (2) Add 10 mL of 97% 3-aminopropyltrimethoxysilane, and then slowly add 7 mL of 1 M NaBH4 aqueous solution in an ice water bath at a rate of 0.3 mL min -1 , so that RuCl3 is reduced to Ru elemental substance; after stirring for 4 hours, Ru will be adsorbed on oxygen defects and nucleate and grow in situ;

[0077] (3) The precursor material obtained in the above step was filtered, washed and dried, and then annealed at 350° C. for 2 h in a 5% hydrogen-argon environment (a hydrogen-argon mixed gas with a hydrogen volume ratio of 5%) to improve crystallinity;

[0078] (4) Finally, annealing was performed at 350℃ for 2h in air to form metal oxide nanoskin and obtain the product Ti n O 2n-1 / Ru / RuO2 composite materials.

[0079] Physical property test:

[0080] The Ti prepared in this step n O 2n-1 / Ru / RuO2 composite materials were subjected to X-ray diffraction (XRD) and scanning electron microscopy (SEM) tests, and the results were as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen from the XRD pattern that the Ti prepared in Example 1 n O 2n-1 The XRD pattern of the Ru / RuO2 composite material matches the standard cards of Ti4O7, RuO2 and Ru, indicating that the prepared composite material is a composite of Ti4O7, RuO2 and Ru. Figure 4 It can be seen from the figure that the Ti4O7 / Ru / RuO2 composite material prepared in Example 1 has RuO2 / Ru nanoparticles with a size of about 5 nm coated on the outside of the Ti4O7 nanotubes.

[0081] The preparation flow chart of this embodiment is as follows Figure 5 As shown, a Ti4O7 / NF carrier is first prepared, and then a Ti4O7 / Ru composite material is prepared. Then, an oxidation layer is formed on the outer layer through an oxidation step in air to obtain a Ti4O7 / Ru / RuO2 composite material.

[0082] Example 2

[0083] 1. Preparation of Tin O 2n-1 / NF vector

[0084] The Ti n O 2n-1 Preparation of / NF vector, the specific steps include:

[0085] (1) Preparation of electrospinning solution: 2 mL of tetrabutyl titanate, 1.2 g of polyvinyl pyrrolidone, and 0.2 g of polystyrene were added to a mixed solution of 5 mL of methanol and 3 mL of acetic acid;

[0086] (2) Electrospinning: Electrospinning was performed at an applied voltage of 17 kV and a feed rate of 0.4 mL / h;

[0087] (3) Pre-oxidation: heating to 280°C in air for 2 h;

[0088] (4) Annealing reduction: Heat to 1000°C in a hydrogen-argon mixed gas (hydrogen volume ratio is 5%) for 2 hours to obtain the product Ti n O 2n-1 / NF carrier material, specifically Ti4O7 / NF carrier.

[0089] 2. Preparation of Ti n O 2n-1 / Ru catalyst

[0090] (1) 50 mg Ti prepared by electrospinning and high temperature reduction in the above step n O 2n-1 NF was dispersed in 10 mL of 0.1 M RuCl 3 aqueous solution in water;

[0091] (2) Add 10 mL of 97% 3-aminopropyltrimethoxysilane, and then slowly add 7 mL of 1 M NaBH4 aqueous solution in an ice water bath at a rate of 0.3 mL min -1 , so that RuCl3 is reduced to Ru elemental substance; after stirring for 4 hours, Ru will be adsorbed on oxygen defects and nucleate and grow in situ;

[0092] (3) The precursor material obtained in the above step was filtered, washed and dried, and then annealed at 350° C. for 2 h in a 5% hydrogen-argon environment to improve crystallinity and maintain the metallic state.

[0093] Physical property test:

[0094] The composite material prepared in this step was subjected to X-ray diffraction (XRD) test, and the results were as follows: Figure 6 As shown. Figure 6 It can be seen from the XDR spectrum that the TinO prepared in Example 2 2n-1The XRD pattern of the / Ru composite matched that of standard Ti4O7 and Ru cards, indicating that the prepared composite material is a complex of Ti4O7 and Ru, namely Ti4O7 / Ru. Because the final annealing and calcination in air was not performed, a RuO2 layer was not formed on the surface of the precious metal Ru.

[0095] Comparative Example 1

[0096] Preparation of TiO2 / NF:

[0097] (1) Preparation of electrospinning solution: 2 mL of tetrabutyl titanate, 1.2 g of polyvinyl pyrrolidone, and 0.2 g of polystyrene were added to a mixed solution of 5 mL of methanol and 3 mL of acetic acid, respectively;

[0098] (2) Electrospinning: Electrospinning was performed at an applied voltage of 17 kV and a feed rate of 0.4 mL / h;

[0099] (3) Pre-oxidation: Heat to 280°C in air for 2 hours.

[0100] Physical property test:

[0101] The composite material prepared in this step was subjected to X-ray diffraction (XRD) test, and the results were as follows: Figure 7 As shown. Figure 7 The XDR pattern of the composite material prepared in Comparative Example 1 shows that the XRD pattern matches that of a standard TiO2 card, so Comparative Example 1 produces TiO2 / NF. Due to the lack of annealing in a reducing atmosphere, a non-stoichiometric titanium oxide / NF support material could not be prepared.

[0102] Comparative Example 2

[0103] Preparation of TiO2 / Ru / RuO2 catalyst

[0104] (1) 50 mg of TiO2 / NF prepared by electrospinning in Comparative Example 1 was dispersed in 10 mL of 0.1 m RuCl3 aqueous solution;

[0105] (2) Add 10 mL of 97% 3-aminopropyltrimethoxysilane, and then slowly add 7 mL of 1 M NaBH4 aqueous solution in an ice water bath at a rate of 0.3 mL min -1 , so that RuCl3 is reduced to Ru elemental substance, and stirred for 4h, Ru will be adsorbed on oxygen defects, nucleating and growing in situ;

[0106] (3) The precursor material obtained in the above step was filtered, washed and dried, and then annealed at 350° C. for 2 h in a 5% hydrogen-argon environment to improve crystallinity.

[0107] (4) Annealing at 350 °C for 2 h in air environment to form metal oxide nanoskin.

[0108] Physical property test:

[0109] The composite material prepared in this step was subjected to X-ray diffraction (XRD) test, and the results were as follows: Figure 8 As shown. Figure 8 The XDR spectrum of the composite material prepared in Comparative Example 2 shows that the XRD pattern matches the standard cards of TiO2, RuO2, and Ru. Therefore, Comparative Example 2 produces TiO2 / Ru / RuO2. A non-stoichiometric titanium oxide / Ru / RuO2 composite material was not produced, but a stable transition metal oxide TiO2 / Ru / RuO2 composite material was obtained.

[0110] Effect embodiment

[0111] 1. The electrochemical performance of the products obtained in each embodiment and comparative example was tested. The specific testing method is as follows:

[0112] The electrochemical performance of the products prepared in each embodiment and comparative example was systematically tested using a three-electrode system. The electrolyte was a 0.5 M H2SO4 solution (pH ≈ 0). The working electrode was a glassy carbon electrode with a diameter of 3 mm, and the catalyst loading was controlled to be 0.2 mg cm -2 The reference electrode was a saturated calomel electrode (SCE), and the counter electrode was a platinum sheet. All test potentials were converted to relative to the reversible hydrogen electrode (RHE). The electrolyte was first purged with nitrogen to remove dissolved oxygen, followed by linear sweep voltammetry (LSV) measurements at a scan rate of 5 mV / s over a potential range of 1.0–1.6 V (vs. RHE).

[0113] The results are as follows Figure 9 As shown, the electrochemical polarization curves of the electrocatalysts prepared in the examples and comparative examples in a three-electrode reaction cell in 0.5MH2SO4 electrolyte; Figure 9 It can be seen that the catalyst prepared in Example 1 shows the best current density, and a lower overpotential can drive 10 mA cm -2 The overpotential of the comparative examples 1 and 2, which were not reduced to a non-stoichiometric ratio by electrolysis of water at a current density of 0.040 W / m, was much higher than that of the embodiment 1, and their electrocatalytic performance was far inferior to that of the embodiments 1 and 2.

[0114] 2. Furthermore, in order to evaluate the durability of the electrocatalyst, the samples were subjected to constant current polarization tests at a current density of 10 mA·cm-2 under the same system, and the voltage changes over time were recorded.

[0115] The results are as follows Figure 10 The figure shows the constant current polarization curves of the electrocatalysts prepared in the examples and comparative examples in a three-electrode reaction cell with a 0.5MH2SO4 electrolyte at a current density of 10 mA. Figure 10 From the constant current polarization curve, it can be seen that Example 1 with RuO2 coating can be maintained for more than 200 hours under acidic conditions, while Example 2 without RuO2 coating has relatively poor stability.

[0116] Therefore, by oxidizing the outer layer of Ru, Ir, and Pd into RuO2, IrO2, and PdO, the internal Ru, Ir, and Pd elements can be wrapped up, and the oxidation and dissolution of Ru, Ir, and Pd inside the organization can be prevented, thereby improving the service life. Moreover, the oxidation temperature of Ti4O7 is above 400°C, and the oxidation of Ru, Ir, and Pd does not cause the non-stoichiometric ratio of transition metal oxides (Ti n O 2n-1 、W n O 3n-1 、Mo n O 3n-1 、Mn n O 2n-1 or Ce n O 2n-1 ) oxidation and reduce conductivity.

[0117] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various variations or modifications within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a non-stoichiometric nanotube-supported electrocatalyst based on electrospinning, characterized in that: The steps include: S1, dissolving an organic compound of a transition metal or a transition metal salt and an electrospinning raw material in an organic solvent, and mixing them uniformly to obtain an electrospinning solution; S2, electrospinning the electrospinning solution to obtain a transition metal oxide support precursor; S3, annealing and pre-oxidizing the transition metal oxide support precursor in air to obtain transition metal oxide / CNF; S4, annealing the transition metal oxide / CNF in a reducing atmosphere to perform a reduction reaction to obtain a non-stoichiometric transition metal oxide / NF support material; S5, adding a non-stoichiometric ratio of transition metal oxide / NF support material to a noble metal salt solution for dispersion to obtain a mixed dispersion; S6. Add a surfactant to the mixed dispersion, and slowly add a reducing agent in an ice-water bath to obtain a precursor solution; S7. Filter the precursor solution, wash and dry it, and then anneal it in a reducing atmosphere to obtain the product.

2. The preparation method according to claim 1, characterized in that The preparation method further comprises: S8. Oxidatively calcining the product obtained in step S7 in an air atmosphere.

3. The preparation method according to claim 1 or 2, characterized in that In step S1, the transition metal is selected from any one of titanium, tungsten, molybdenum, manganese, and cerium; the organic compound or transition metal salt of the transition metal is selected from any one of organic titanium compounds, tungstates, molybdates, manganates, and cerates; In step S2, the transition metal oxide support precursor is selected from any one of an organic titanium compound / CNF, a tungstate / CNF, a molybdate / CNF, a manganate / CNF, and a cerate / CNF; In step S4, the non-stoichiometric transition metal oxide / NF support material is selected from Ti n O 2n-1 / NF、W n O 3n-1 / NF、Mo n O 3n-1 / NF、Mn n O 2n-1 / NF、Ce n O 2n-1 / NF, where n is an integer from 1 to 4.

4. The preparation method according to claim 1 or 2, characterized in that The electrospinning raw material includes polyvinyl pyrrolidone and any one of polystyrene, polymethyl methacrylate, polylactic acid, polyvinyl alcohol, and polyacrylonitrile; and / or the organic solvent is a mixed solvent of methanol and acetic acid, and the volume ratio of the two is 4:3 to 6:

3.

5. The preparation method according to claim 1 or 2, characterized in that In step S3, the annealing pre-oxidation treatment is performed at a temperature of 250 to 300° C. for 1.5 to 3 hours. And / or, in step S4, the annealing temperature is 900-1100° C., and the time is 1-3 hours.

6. The preparation method according to claim 1 or 2, characterized in that In step S4 and / or step S7, the reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume ratio of hydrogen is 5-20%.

7. The preparation method according to claim 1 or 2, characterized in that In step S5, the noble metal is selected from any one of Ru, Ir, and Pd; the noble metal salt is selected from any one of RuCl3, IrCl3, and PdCl2; and the concentration of the noble metal salt solution is 0.05 to 0.2 M; The mass volume ratio of the non-stoichiometric transition metal oxide / NF carrier material to the noble metal salt solution is (30-70) mg: (5-20) mL.

8. The preparation method according to claim 1 or 2, characterized in that The surfactant is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and hexadecyltrimethylammonium bromide; And / or, the reducing agent is selected from at least one of sodium borohydride and sodium citrate.

9. The preparation method according to claim 1 or 2, characterized in that: In step S7, the annealing temperature is 300-500° C. and the time is 1-3 hours; The product obtained in step S7 is a non-stoichiometric transition metal oxide / NF loaded noble metal nanoparticle electrocatalyst selected from Ti n O 2n-1 / Ru、Ti n O 2n-1 / Ir、Ti n O 2n-1 / Pd、W n O 3n-1 / Ru、W n O 3n-1 / Ir、W n O 3n-1 / Pd、Mo n O 3n-1 / Ru、Mo n O 3n-1 / Ir、Mo n O 3n-1 / Pd、Mo n O 3n-1 / Ru、Mo n O 3n-1 / Ir、Mn n O 2n-1 / Pd、Ce n O 2n-1 / Ru、Ce n O 2n-1 / Ir、Ce n O 2n-1 / Pd, wherein n is an integer from 1 to 4.

10. The preparation method according to claim 2, characterized in that In step S8, the calcination temperature is 300-500° C. and the time is 1-3 hours; The product obtained in step S8 is a non-stoichiometric ratio of transition metal oxide / NF loaded noble metal oxide nanoskin coated noble metal nanoparticles electrocatalyst, selected from Ti n O 2n-1 / Ru / RuO2、Ti n O 2n-1 / Ir / IrO2、Ti n O 2n-1 / Pd / PdO2, W n O 3n-1 / Ru / RuO2、W n O 3n-1 / Ir / IrO2、W n O 3n-1 / Pd / PdO2、Mo n O 3n-1 / Ru / RuO2、Mo n O 3n-1 / Ir / IrO2、Mo n O 3n-1 / Pd / PdO2、Mn n O 3n-1 / Ru / RuO2、Mn n O 3n-1 / Ir / IrO2、Mn n O 3n-1 / Pd / PdO2、Ce n O 2n-1 / Ru / RuO2、Ce n O 2n-1 / Ir / IrO2、Ce n O 2n-1 Any one of / Pd / PdO2.

11. A non-stoichiometric nanotube-supported electrocatalyst prepared by the preparation method according to any one of claims 1 to 10, wherein the non-stoichiometric nanotube-supported electrocatalyst is an electrocatalytic oxygen evolution catalyst.